Environmental crime in Europe - Farmer, Andrew; Faure, Michael G.; Vagliasindi, Grazia Maria Veronica (Modern studies in European law, 2017)
European environmental law and environmental crime : an introduction / Teresa Fajardo -- EU harmonisation competences in criminal matters and environmental crime / Giovanni Grasso -- The EU environmental crime directive / Grazia Maria Vagliasindi -- Environmental criminal law in France / Floriana Bianco and Annalisa Lucifora -- Environmental criminal law in Germany / Stephan Sina -- Environmental criminal law in Italy / Grazia Maria Vagliasindi -- Environmental criminal law in Poland / Karolina Jackowicz, Malgosia Fitzmaurice and Valsamis Mitsilegas -- Environmental criminal law in Spain / Juan Luis Fuentes Osorio -- Environmental criminal law in Sweden / Michael Faure and Niels Philipsen -- Environmental criminal law in the United Kingdom / Elena Fasoli -- The evolution of environmental criminal law in Europe : a comparative analysis / Michael Faure -- Environmental crime in Europe : state of affairs and future perspectives / Andrew Farmer, Michael Faure and Grazia Maria Vagliasindi